Analysis of Slotted and Slotless Permanent Magnet DC Motor for Drone Applications. - Johari, Affifuddin; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2022)
When it comes to choosing BLDC motors, the advantages and disadvantages of slotted brushless DC motors (BLDC) and slotless BLDC might be confusing. The goal of this study was to use JMAG-Designer Software to define the characteristics of slotted and slotless BLDCs. The results of this study revealed that slotted BLDC produces more torque than slotless BLDC. The power output of slotted and slotless BLDCs was nearly identical, but the slotless BLDC’s speed was ten times faster than the slotted BLDC’s. Because slotted BLDCs produced greater ripple torque than slotless BLDCs, slotted BLDCs vibrated more than slotless BLDCs.